TRENDS IN THE EVENT NARCISSISTIC NURSING STUDENT OF USING INSTAGRAM - Baginda Perwira Indra Teja; Hasmilla Sari (Jurnal Ilmiah Mahasiswa Fakultas Keperawatan, 2018)
Starting from custom upload personal activities impact on the trend called narcissistic personality, that personality disorder in which individuals show an attitude of self love excess. The attitude shown in individuals with this tendency does not conform with the qualifications of nursing students, as a nurse should be able to interact with anyone, have a sense of empathy, and dealing without the benefit of others. The purpose of this study is to see the level of incidence of the narcissistic tendencies in students of the Faculty of Nursing, University of Syiah Kuala who use social networking media instagram. This study was performed on 27 to 30 June 2016. This research is a descriptive cross sectional study design. The sampling technique purposive sampling with a sample of 87 respondents. Mechanical methods of collecting data is by using an online survey to all students of the Faculty of Nursing, University of Syiah Kuala with education level S1, and use directly as well as via telephone interviews in the form of Likert scale consists of 21 statements. Methods of data analysis using frequency distribution. The result showed the level of narcissistic tendency of students of the Faculty of Nursing, University of Syiah Kuala who use social networks Instagram that are in the low category with 54 respondents (64.4%). Expected in nursing students who use social networking instagram not expose private activities and specific body areas on instagram.